Anorganisch‐organische Hybridschichten für die Entspiegelung optischer Oberflächen. (June 2015) - Schulz, Ulrike; Munzert, Peter; Rickelt, Friedrich; Präfke, Christiane; Gratzke, Nancy; Knopf, Heiko; Wolleb, Sabrina; Kaiser, Norbert
<x xml:space="preserve">Abstract</x> Inorganic‐organic hybrid coatings for antireflection of optical surfaces The application of nanostructures for optical surfaces has been discussed since antireflective nanostructures have been discovered on the eyes of night‐flying insects. On injection molded plastic lenses, antireflective nanostructures can easily be produced by plasma etching. The procedure has now been adapted to vacuum evaporated organic layers. Complex coatings composed of inorganic layers and organic nanostructures are especially suitable for realizing broadband antireflection properties on glass lenses.